Effects of ospemifene on vaginal epithelium of post-menopausal women. (2nd December 2017) - Alvisi, Stefania; Baldassarre, Maurizio; Martelli, Valentina; Gava, Giulia; Seracchioli, Renato; Meriggiola, Maria Cristina
Abstract: Ospemifene is a selective estrogen receptor modulator used for the treatment of vulvo-vaginal atrophy (VVA) in post-menopausal women. No direct evidence of its effects on histological features of the human vagina has been reported. To evaluate the effects of ospemifene on histological parameters, glycogen content, proliferation, and estrogen receptor α expression (ERα) of vaginal epithelium in post-menopausal women. Thirty-two post-menopausal women undergoing surgical procedures were enrolled. Sixteen subjects taking ospemifene at the time of inclusion (OSP) were compared to 16 subjects not taking any hormone (CTL). Vaginal biopsies were taken from the proximal and distal vaginal wall during surgery to evaluate histology, Ki-67 and ERα expression. OSP group showed thicker vaginal epithelium (349 ± 64 vs. 245 ± 53 μm, p < .001), higher proliferation index (212 ± 47 vs. 127 ± 28 Ki-67 + cells/mm, p < .001), higher epithelial (27.3 ± 3.1 vs. 20.6 ± 2.9 score, p < .001) and stromal (26.6 ± 4.9 vs. 20.6 ± 2.6 score, p < .001) ERα expression when compared to the CTL group. In postmenopausal women affected by VVA, 1 month intake of ospemifene is associated with an increased maturation, and ERα expression of the vaginal mucosa. These changes may partially explain the improvement of symptoms of vaginal atrophy reported with this drug.